2017
DOI: 10.5901/jesr.2017.v7n1p35
|View full text |Cite
|
Sign up to set email alerts
|

“... As Long as Power Relations Exist ... Yes, There are Inequalities…” Social and Educational Inequalities in Greece According to the Views of Female and Male Students of Tertiary Education Institutions

Abstract: The issue of social and more specifically educational inequalities in Greek society and education seems to concern the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The researchers opted for a university sample, in order to record the attitudes and views of young people who are believed to be "favored" by the educational system. The analysis showed that the sample believes that, indeed, there is inequality in Greek society, as well as in Greek education, and can identify a big number of signs of the phenomenon (Kyridis, Tourtouras, & Thanos, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers opted for a university sample, in order to record the attitudes and views of young people who are believed to be "favored" by the educational system. The analysis showed that the sample believes that, indeed, there is inequality in Greek society, as well as in Greek education, and can identify a big number of signs of the phenomenon (Kyridis, Tourtouras, & Thanos, 2017).…”
Section: Discussionmentioning
confidence: 99%